Community Empowerment Based on Local Potential Through Chayote Cracker Production in Pagar Dewa Village - Wike Nurwita Dewi; Bayurini Puji Lestari (Jurnal Inovasi Kerja Nyata, 2026)
Community empowerment based on local potential is an important strategy in increasing economic independence and the welfare of rural communities. This study aims to examine the process of community empowerment through the use of chayote (Sechium edule) as an alternative raw material in cracker production. The method used is a qualitative approach with observation, interviews, and documentation techniques with community groups involved in the local food processing program. The results show that the use of chayote as a cracker ingredient can increase the added value of local commodities, open new business opportunities, and improve community entrepreneurial skills. In addition, this program also encourages the creation of innovative healthy and sustainable food products. In conclusion, chayote cracker production is an effective form of community empowerment based on local potential that is oriented towards the village creative economy.